Nitrate uptake improvement by modified activated carbons developed from two species of pine cones - Nunell, Gisel Vanesa (2015)
Activated carbons from two species of pine cones (Pinus canariensis and Cupressus sempervirens) were prepared by phosphoric acid activation and tested for the removal of nitrate ions from aqueous solution. To investigate the feasibility of improving their nitrate adsorption capacity, two different post-treatments - a thermal treatment and a treatment with saturated urea solution - were also applied to the prepared activated carbons. Comparison of the treated and untreated activated carbons showed that both post-treatments improved the nitrate adsorption performance more than twice. The maximum adsorption capacity, as evaluated from determination of the adsorption isotherms for the P. canariensis based carbons, and their proper representation by the Langmuir model, demonstrated that the post-treatment with the urea solution led to activated carbons with increased nitrate removal effectiveness, even superior to other reported results. Enhancements in their adsorption capacity could be mainly ascribed to higher contents of nitrogen and basic functional groups, whereas porous structure of the activated carbons did not seem to play a key role in the nitrate uptake.